Monitoring Communication Development Between Teachers and Their Students With Congenital Deafblindness: An Application of the Layered Communication Model - Wolthuis, Kirsten; Bol, Gerard W.; Minnaert, Alexander; Janssen, Marleen J. (Frontiers in Education, 2020)
The Layered Communication Model (LCM) consists of three layers of intersubjective development divided into different communicative behaviors per layer. Earlier research showed that the LCM can be used to describe the communication level between teachers and their students with congenital deafblindness (CDB). This study analyzed whether the LCM can also be used to monitor the development of LCM behaviors over time. Videos of eight student-teacher dyads recorded at the start of this study (baseline phase) and five months later (follow-up phase) were coded using 10-second partial interval coding. The presence of the communicative behaviors at the three layers of the LCM during baseline and follow-up were calculated and compared between dyads and phases. The results on the presence of LCM behaviors were in line with earlier research. The presence of primary layer behaviors was comparable between dyads, confirming that this is a basic communication layer. The differences found between dyads in the presence of secondary and tertiary layer behaviors shows that these can be used to determine a dyad’s communicative level. Results also showed that the LCM can be used to monitor communication development. Small increases were found in the presence of LCM behaviors between baseline and follow-up for the primary layer behaviors, but larger increases were found for secondary and tertiary layer behaviors, showing that development can be monitored. In conclusion, this study again showed that the LCM can be used to describe a dyad’s communicative level. We also found increases in the presence of certain behaviors between baseline and follow-up for all dyads, which shows that the LCM can also be used to monitor communication over time. More insight into the period between the analyzed phases is suggested to analyze what might have caused the increase in presence of behaviors. This would reveal more about the use of the LCM as a tool to improve communication development.